2022
DOI: 10.36681/tused.2022.112
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical ımplication of spatial visualization: A correlate of students’ achievements in physics

Abstract: This study investigated pedagogical implication of spatial visualization as correlate of students’ achievement in physics. Ex post facto research of the co-relational type with 857 senior secondary school three (S. S. 3) participants comprising of male and female students from both public and private-schools from Kwara State, Nigeria. Four research questions with corresponding hypotheses were raised and answered in this study. Pro forma of physics result of respondents at WASSCE formed the achievement componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This trend confirmed a significant correlation between FMA and students' performance in physics as exposed in the analysis and further substantiated by the works of Okye and Gladysibibo (2015) and Abubakar et al (2015). The state of affairs in research parlance have posited fairly in the ability of both male and female learner (Badmus & Jita, 2022;Baldwin et al, 2016). In this study, more male students offered further mathematics than female students in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend confirmed a significant correlation between FMA and students' performance in physics as exposed in the analysis and further substantiated by the works of Okye and Gladysibibo (2015) and Abubakar et al (2015). The state of affairs in research parlance have posited fairly in the ability of both male and female learner (Badmus & Jita, 2022;Baldwin et al, 2016). In this study, more male students offered further mathematics than female students in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The responsibility of school fees payment lies with the parents in private schools and are more involved in the decision making than parents whose wards attend public schools (Olatoye & Agbatogun, 2009). Gender debate in the classroom and it influence on students' performance abound in the literature for years (Badmus & Jita, 2022;Baldwin et al, 2016). Studies have argued for and against male and female students in terms of capacity for classroom activities (Badmus & Jita, 2022;Baldwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomas, & Israel, (2013) concluded that the Polya heuristic way of addressing problems is an alternate teaching approach that can improve students' current physics performance, especially when regular laboratories are hard to come by. Badmus, & Jita, (2022) suggested that teaching methods that encourage visualization should be used to enhance students' achievement in physics.…”
Section: Instructional Methodsmentioning
confidence: 99%
“…This situation is prevalent among female learners, teachers and experts. A body of literature traversed barriers to learning physics by female students with the intension to substantiate primordial deficiencies with no success (Barthelemy et al, 2015;Traxler, 2016;Badmus & Jita, 2022). A field without adequate gender representation is considered as male dominated and not necessarily female incapacitated.…”
Section: Introductionmentioning
confidence: 99%